PERAN ASEAN SENIOR OFFICIAL ON DRUG MATTERS DALAM MENAGGULANGI DRUGS TRAFFICKING DI INDONESIA TAHUN 2020 – 2025 - Roza Andriani; Muhammad Rizki Firzani (LPPM Universitas Abdurrab, 2023)
ABSTRACT This article examines Asean Senior Official On Drug Matters initiatives in combating and drugs traficiking abuse which has reached the level of ‘drugs emergency. That is why IRs begins to broaden and deepen its object of discussion to non-military topics, such as economics, politics, social, and environment. In a brief, IRs discourse moves from state security to human security In the future, continuous evaluation is needed to assure that the policy is well implemented and provides impact as is expected, which is to decrease the number of drug abusers. the ASEAN began to implement a shared commitment related to drug abuse contained in the implementation plan to realize the Drug-Free ASEAN 2015 then continues to the Work Plan on Securing Communities Against Illicit Drugs 2016 - 2025. this article lack of legitimacy to make legal binding decisions.